Splicing dysregulation contributes to the pathogenicity of several F9 exonic point variants. Issue 8 (30th June 2019) - Katneni, Upendra K.; Liss, Aaron; Holcomb, David; Katagiri, Nobuko H.; Hunt, Ryan; Bar, Haim; Ismail, Amra; Komar, Anton A.; Kimchi‐Sarfaty, Chava
Abstract: Background: Pre‐mRNA splicing is a complex process requiring the identification of donor site, acceptor site, and branch point site with an adjacent polypyrimidine tract sequence. Splicing is regulated by splicing regulatory elements (SREs) with both enhancer and suppressor functions. Variants located in exonic regions can impact splicing through dysregulation of native splice sites, SREs, and cryptic splice site activation. While splicing dysregulation is considered primary disease‐inducing mechanism of synonymous variants, its contribution toward disease phenotype of non‐synonymous variants is underappreciated. Methods: In this study, we analyzed 415 disease‐causing and 120 neutral F9 exonic point variants including both synonymous and non‐synonymous for their effect on splicing using a series of in silico splice site prediction tools, SRE prediction tools, and in vitro minigene assays. Results: The use of splice site and SRE prediction tools in tandem provided better prediction but were not always in agreement with the minigene assays. The net effect of splicing dysregulation caused by variants was context dependent. Minigene assays revealed that perturbed splicing can be found. Conclusion: Synonymous variants primarily cause disease phenotype via splicing dysregulation while additional mechanisms such as translation rate also play an important role. Splicing dysregulation is likely to contribute to the disease phenotype of several non‐synonymous variants. Abstract : Splicing dysregulation is considered the primary disease-inducing mechanism of synonymous variants, but its contribution to the disease phenotype of non-synonymous variants is underappreciated. Through the analysis of F9 exonic point variants using a series of in silico and in vitro splicing analysis tools, we show that while synonymous variants primarily cause disease via splicing dysregulation, additional mechanisms such as altered translation rate also play an important role. Importantly, splicing dysregulation is likely to contribute to the disease phenotype of several non-synonymous variants.